PERAN EDUKASI GIZI BERBASIS BUDAYA DALAM MENINGKATKAN KESADARAN REMAJA TERHADAP ASUPAN MAKANAN LOKAL - Afni Nurvita Sari; Amalia Rahma (Poltekkes Kemenkes Medan, 2024)
Nutritional problems among adolescents in Indonesia, especially in developing areas, are a serious concern with the prevalence of malnutrition reaching 9.2% at the age of 13-15 years. This research aims to analyze the role of culture-based nutrition education in increasing local food consumption and adolescent awareness of food intake. Using a quasi-experimental design, research was conducted in Sugihwaras Village, Tuban Regency, involving 38 teenagers as subjects. The education is carried out through the traditional game called Sri Gendem, which integrates material about teenagers' behavior towards local food. Research shows a significant increase in adolescent behavior toward balanced nutrition and local food consumption after the intervention. These findings indicate that culture-based nutrition education, through an interactive approach, is effective in increasing adolescent nutritional awareness, as well as encouraging the consumption of nutritious local food.